Strategy of Advertising Agencies in India for Evaluating Advertising Effectiveness across Experience - Sofat, Yashmin (Indian Journal of Marketing, 2011)
When the nation’s adventures spend crores of rupees a year for advertising, its effectiveness is a major concern. In some instances, advertising is the largest single cost in a company’s marketing budget, and so the company should want to know what it is getting for its money - whether its advertising is really working. Evaluation is the primary instrument and is a strategy of advertisers to maximize their profits and minimize their cost and expenditure, as agencies have to provide some assurance that their advertising rupees are being spent productively. With the dominant commission system of compensation, where the advertising agency is paid not for what it produces, but for how much media and space time it becomes, all the more important is to have a system of evaluating advertising results. Some measure of advertising effectiveness, therefore, is considered to be an indispensable part of any advertising programme. Advertising management is especially interested in testing, since evidence of advertising productivity is the best justification for advertising expenditure. Tests and measurements are suggested guide posts, enabling the agency to direct their efforts into the most productive channel, and thus improve the returns from advertising.